Urgensi Mobile Learning Berbasis Situs Jejak Gerilya Jenderal Soedirman di Pakisbaru Pacitan sebagai Media Pembelajaran Sejarah Generasi Z - Maghfiroh, Aghnia Muzamilul; Suprapta, Blasisus; sulistyo, wahyu djoko (J-PIPS (Jurnal Pendidikan Ilmu Pengetahuan Sosial), 2021)
This research was conducted to analyze the urgency of history learning media innovation. The development of the times puts history learning to have challenges to be able to adapt the learning targets faced, namely the Z Generation. This generation was born in the early 2000s. The character of this generation is very sensitive to technology and communication, meaning that they have advantages in the field of information and knowledge. Meanwhile, educators who were born in the previous era are still didn't used to it, so that educators often admit to being "gaptek" (stuttering technology). Therefore, this study describes the urgency of developing Mobile Learning media using local historical sites. The description presented covers the development stage of the first part. This section describes a preliminary study to see potential problems and analyze the needs of students in learning history. The results obtained from this study are quite significant with the percentage reaching above 80% for the category of interest in mobile learning media. In the early stages of product development, the materials and media produced from the field research process at the historical site of General Sudirman in Pacitan is also presented. In addition, it also describes the form of the media design as an initial draft with adjustments to the learning interests of the Z Generation. So, Mobile Learning is expected to facilitate the Z Generation in learning history.